Poglobitev zahtev za družbeno odgovorno poročanje gospodarskih družb na ravni EU - Hojnik, Janja (Delavci in delodajalci, 2012)
This article deals with legal aspects of sustainable reporting in the EU. It firstly explores the state of affairs in sustainability reporting regulation and points out recent increased support for integrated reporting. In the second part of the article, EU rules in this field are discussed-both. Current state of affairs is presented as well as open questions and legal alternatives for more effective and workers-friendly regulation are deliberated.
Keywords: družbena odgovornost; Evropska unija; gospodarske družbe; podjetja; zaposleni